Structure and performance control of porous Si3N4 ceramics fabricated by freeze-drying process. Issue 6 (15th March 2021) - Sun, Mengyong; Yang, Shuangyan; Gao, Xiaoju; Man, Peng; Qu, Junfeng; Zhang, Wu; Yin, Shaoqing; Cheng, Laifei
Abstract : Effects of glycerin and silica sol on the structure and performance of porous Si3 N4 ceramics that were prepared via freeze-drying were studied. Adding glycerol affected growth process of ice crystals, changed pore structural from bimodal peaks to triple peaks distribution, and formed regular honeycomb structure. This improved mechanical properties and electromagnetic wave transmission properties of Si3 N4 ceramics. Therefore, adding glycerol changed mesoscopic morphology of the material. For porous Si3 N4 ceramics with 72.5% porosity, flexural strength was 38 MPa, compressive strength was 42.6 MPa, and dielectric constant was 1.75 in the frequency range of 12.4–18 Hz as the amount of added glycerol increasing to 5 wt%. By reducing the sintering eutectic point of the system, the addition of silica sol promoted sintering shrinkage and formed new phases. Thus, pore size distribution was changed from bimodal to unimodal. Moreover, dielectric constant of samples increased from 2.25 to 3.5. Finally, structure and performance of porous Si3 N4 ceramics were controlled via addition of glycerol and silica sol.